VD_FINDINFO ML / 2012 / 76 vom 10. April 2012 - VD Tribunal cantonal (2012)
MOTIVATION DE LA DÉCISION, DISPOSITIF, DÉLAI, VOIE DE DROIT PRÉMATURÉE, FORMALISME EXCESSIF | 107 al. 2 CPC (CH), 132 al. 1 CPC (CH), 132 al. 2 CPC (CH), 239 al. 2 CPC (CH), 321 CPC (CH), 56 CPC (CH)